Video signal transmission via optical fiber communication system - Abu Dawoud, Sawsan; al_Khayyat, Mervat (جامعة بوليتكنك فلسطين - اتصالات, 2010)
This project aims to transmit video signal through fiber optic system, this system consists of transmitter, receiver and the optical fiber as communication channel. In the system the video file will be divided into frames using matlab software to send one frame at a time which any lost in data at any time will not affect the all system performance, these pictures are taken from PC in Ethernet format, then this out coming signal should be converted to serial using wiz110sr to inter the digital optical system (transmitter and receiver) which is serial channel. Then this data through the optical transmitter and travel in the fiber then to be detected in the receiver is in serial form, and before it come to the receiver pc it should convert to Ethernet form using another wiz110sr board. The received pictures are collected to form the video file by using matlab software, lastly the video is displayed. To convert the Ethernet data to serial data and versa by using wiz110sr board, we need to choose the operation mode of wiznet, also the network configuration such as IP address and port number should be specified, and the serial configuration must be the same at the two wiz110sr board and this configuration should be suitable for optical system
no of pages 62, اتصالات 9/2010
Keywords: Video signal; optical fiber communication system